2010
DOI: 10.1007/s00439-010-0856-x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective variants screening of connexin genes in children with hearing impairment: genotype/phenotype correlation

Abstract: The crucial role of gap junctions, which are composed of connexin (CX) protein, in auditory functions has been confirmed by numerous studies. In this study, we investigate the prevalence and phenotype/genotype correlation of connexin (CX) gene family variants in a cohort of children with nonsyndromic hearing loss (HL). A total of 253 unrelated children with nonsyndromic HL were screened for the presence of variants in 6 genes of the CX gene family. The prevalence of CX gene variants in 253 patients was 19.7% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…A previous investigation showed that mouse Cx29 did not induce intercellular conductances when expressed alone in mouse neuroblastoma cells [12]. Our earlier study established that mutations of GJC3 are associated with nonsyndromic hearing loss [17,18]. Moreover, our data demonstrate that the p.E269D missense mutation of CX30.2/CX31.3 results in the accumulation of the CX30.2/CX31.3 mutant protein in the endoplasmic reticulum, rather than in the cytoplasmic membrane [19].…”
Section: Introductionmentioning
confidence: 43%
“…A previous investigation showed that mouse Cx29 did not induce intercellular conductances when expressed alone in mouse neuroblastoma cells [12]. Our earlier study established that mutations of GJC3 are associated with nonsyndromic hearing loss [17,18]. Moreover, our data demonstrate that the p.E269D missense mutation of CX30.2/CX31.3 results in the accumulation of the CX30.2/CX31.3 mutant protein in the endoplasmic reticulum, rather than in the cytoplasmic membrane [19].…”
Section: Introductionmentioning
confidence: 43%
“…Few studies have been conducted on the correlation of variants in the GJB4 gene and its phenotype in patients with nonsyndromic hearing loss. These previous studies were compared and summarized in Table I (13,19,20). In these results, the proportion of patients with GJB4 variants was determined to be 4.09% (21/513).…”
Section: Discussionmentioning
confidence: 99%
“…In the study, five amino acid variants (c.307 C>T, c.371 G>A, c.478 C>T, c.507 C>G and c.611 A>C) were detected in deaf individuals without skin disorders (19). In our previous genetic survey of 373 individuals, including 253 with nonsyndromic deafness and 120 with normal hearing, 11 mutations were detected in the patients with hearing loss (20). However, the correlation between the GJB4 gene mutations and the audiology phenotype in deaf patients was not examined.…”
Section: Introductionmentioning
confidence: 93%
“…In the majority of studies which researched the mutations associated with prelingual hearing impairment in the Taiwanese population, the hearing-impaired subjects were mainly recruited from students of the rehabilitation schools for the deaf [12][13][14][15]. Some of the studies purely focused on the GJB2 gene [12,13], or targeted only a few deafness-associated mutations [16].…”
Section: Introductionmentioning
confidence: 99%